Prophylactic Erythropoietin for Neuroprotection in Very Preterm Infants: A Meta-Analysis Update - Fischer, Hendrik S.; Reibel, Nora J.; Bührer, Christoph; Dame, Christof (Frontiers in Pediatrics, 2021)
A meta-analysis update of randomized controlled trials investigating recombinant human erythropoietin suggests improved neurodevelopmental outcome in preterm infants. There was substantial heterogeneity, which could be ascribed to a single trial. Exclusion of this trial featuring a high risk of bias abolished heterogeneity and any effects of recombinant human erythropoietin treatment.